Frequency‐swept high‐repetition rate optical source. Issue 9 (8th April 2020) - Finot, Christophe
Abstract: We propose and numerically validate an all‐optical scheme to generate optical pulse trains with varying temporal pulse‐to‐pulse delay and pulse duration. Our simulations confirm that applying a temporal sinusoidal phase modulation followed by a shaping of the spectral phase is efficient to maintain high‐quality Gaussian temporal profiles.